2008
DOI: 10.21836/pem20080302
|View full text |Cite
|
Sign up to set email alerts
|

The therapy of horses with back problems in a thermium

Abstract: ZusammenfassungEs sollte herausgefunden werden, ob die Behandlung von Pferden mit Rückenbeschwerden in einem Thermium mit Infrarot-C-Strahlung sinnvoll ist und ob mit Hilfe klinischer und weiterführender Untersuchungen ein Ergebnis nachgewiesen werden kann. 20 Pferde mit Rük-kenbeschwerden wurden jeweils 14 Tage lang täglich in einem Thermium mit Infrarot-C-Strahlung behandelt (Testgruppe) und danach eine halbe Stunde longiert. Eine Kontrollgruppe von 10 Pferden wurde in dieser Zeit ausschließlich longiert. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
1
0
2
Order By: Relevance
“…As the rubber is expected to have some elasticity, and this elasticity might potentially be variable in different temperatures, we elected to use the hard and stable material of aluminium for our investigation. Other algometry investigations have used tips of 2 mm to 14 mm in diameter [3, 10, 11, 23], and these results cannot be directly compared with the results of the present study, as the effect of surface area could be clearly shown. Smaller tips reduced the pressure threshold in the present study as well as in previously published studies [23, 27] and they also created the most consistent results.…”
Section: Discussionmentioning
confidence: 56%
“…As the rubber is expected to have some elasticity, and this elasticity might potentially be variable in different temperatures, we elected to use the hard and stable material of aluminium for our investigation. Other algometry investigations have used tips of 2 mm to 14 mm in diameter [3, 10, 11, 23], and these results cannot be directly compared with the results of the present study, as the effect of surface area could be clearly shown. Smaller tips reduced the pressure threshold in the present study as well as in previously published studies [23, 27] and they also created the most consistent results.…”
Section: Discussionmentioning
confidence: 56%
“…Die Behandlung mit Infrarot kann mithilfe von Strahlungskabinen ( Abb. 5 ) oder Laserapplikation erfolgen 43 , 44 .…”
Section: Infrarottherapieunclassified
“…Bei fast allen Punkten zeigten die Pferde, die mit Infrarot behandelt wurden, im Vergleich zur Kontrollgruppe, hoch- (p ≤ 0,01) bis höchst- (p ≤ 0,001) signifikante Besserungen . Es ist jedoch nicht auszuschließen, dass im Speziellen bei der Palpation und den Provokationsproben ein Gewöhnungseffekt eingetreten ist 43 .…”
Section: Infrarottherapieunclassified